ANALISIS KELAYAKAN DAN PROFITABILITAS AGROINDUSTRI KERIPIK DI DESA MANE TUNONG KECAMATAN MUARA BATU KABUPATEN ACEH UTARA ( Studi Kasus Agroindustri Keripik Kelompok Wanita Tani Bungong Mane) - Rezky, Ryan Aditya; Zuriani, Zuriani; Puarada, Sakral Hasby; Adhiana, Adhiana; Suryadi, Suryadi (LPPM Universitas Malikussaleh - Indonesia, 2024)
KWT Bungong Mane is an UMKM that produces products made from agricultural commodities, namely tempeh chips, potato sticks and purple cassava sticks. KWT Bungong Mane is located in Mane Tunong Village, Muara Batu District, North Aceh Regency. This research aims to analyze the feasibility of the KWT Bungong Mane chips agroindustry in Mane Tunong Village, Muara Batu District, North Aceh Regency and analyze the level of profitability in the KWT Bungong Mane chips agroindustry in Mane Tunong Village, Muara Batu District, North Aceh Regency. The method used in this research is feasibility and profitability analysis. The results of this research obtained an R/C ratio value of 1.43. A value of 1.43 > 1 indicates that the KWT Bungong Mane chips agroindustry is worthy of cultivation based on the R/C ratio criteria. A value of 1.43 can be interpreted as if every cost incurred by the business owner is Rp. 1, the business owner will receive income of Rp. 1.43. Then, based on the profitability calculation results, it can be seen that the margin of safety (MOS) value is 91.82% and the margin income ratio (MIR) value is 32.99%. From the calculation of the MOS and MIR values, the profitability of the KWT Bungong Mane chips agroindustry is obtained at 30.29% or the equivalent of IDR 2,480,751/month, this shows that the increase in prices of the main raw materials that occurred in the KWT Bungong Mane chips agroindustry is still safe. and has good prospects for business and development because it is able to generate profits. Keywords: feasibility, margin of safety, margin income ratio, protability